METHODICAL METHODS FOR DEVELOPING STUDENTS' SPEECH IN MOTHER TONGUE AND LITERACY CLASSES - Yusupbayeva Lobar Alisherovna (European Science Publishing, 2024)
This article discusses the development of oral speech among primary school students. It emphasizes that speech is not only about correct grammatical usage of language but also about developing skills to express thoughts clearly, logically, and aesthetically. The article explores methods to expand vocabulary, improve logical thinking skills, and enhance communicative competence through modern textbooks and assignments. Additionally, it high lights the importance of extracurricular activities, didactic games, and dramatized tasks in fostering creativity.
Keywords: Speech culture, primary education, linguistic principle, vocabulary, logical thinking, textbooks, modern trends.